REVIEWING THE BRITISH ENGLISH (BRE) AND AMERICAN ENGLISH (AME) DIALECTS - Dirgeyasa, I Wy (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2015)
Of the many different dialects of English such as British English (hereafter BrE), American English (hereafter AmE), Australian English (AsE), or Canadian English (CnE) or even Singaporean English (hereafter Singlish), etc, the most common widely use across the globe are BrE and AmE. The two dialects of English, as a matter of fact, are dominantly used in any kinds of fields to mention a few such as politics, economics, diplomatic relationship, medical, information communication and technology (ICT), and education as well. The debate about the use of BrE and AmE often centers on education especially in the process of learning and acquiring the English itself because the two dialects of English provide some different and distinctive features. Because of their differences and distinctive features, the learners often find difficulties and often make them confused which one to use. This paper is attempting to review the unique features of BrE and AmE focusing on the spellings.